2021
DOI: 10.1007/s13178-020-00532-z
|View full text |Cite|
|
Sign up to set email alerts
|

Paraphilic Interests: The Role of Psychosocial Factors in a Sample of Young Adults in Hong Kong

Abstract: Background Little is known about the prevalence and nature of paraphilic interests in the Hong Kong young adult population. This study explores the psychosocial factors associated with paraphilic interests. Methods Testing the propositions of several criminological theories (i.e., the theories of self-control, general strain, social learning, social control, and routine activity), the study recruited 1171 participants (18–40 years old), from September 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 102 publications
(94 reference statements)
1
14
0
Order By: Relevance
“…Moreover, an individual's sexual risk-taking tendency was found to be positively associated with his/her development of paraphilic interests. Previous studies have found that individuals who had paraphilic interests or had been diagnosed with paraphilias were more likely to engage in hypersexual activities, such as having multiple sexual partners, a high sexual appetite and preoccupation, and high rates of sexual behavior (Kafka and Hennen, 2003;Långström and Hanson, 2006;Kafka, 2009;Chan, 2021). Indeed, Chan (2020a) found that high levels of RSB and paraphilic interests were significantly associated with sexual offending behavior.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, an individual's sexual risk-taking tendency was found to be positively associated with his/her development of paraphilic interests. Previous studies have found that individuals who had paraphilic interests or had been diagnosed with paraphilias were more likely to engage in hypersexual activities, such as having multiple sexual partners, a high sexual appetite and preoccupation, and high rates of sexual behavior (Kafka and Hennen, 2003;Långström and Hanson, 2006;Kafka, 2009;Chan, 2021). Indeed, Chan (2020a) found that high levels of RSB and paraphilic interests were significantly associated with sexual offending behavior.…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with some theories of sexual offending, Lalumière et al (2005) posited that an individual's paraphilic behavior may be influenced by his/her degree of impulsivity or propensity to engage in sexual and nonsexual risky behavior. Empirical support for the roles of risk-taking and impulsivity in the expression of paraphilic interests and activities has accumulated (e.g., Kafka, 1997Kafka, , 2001Långström and Seto, 2006;Marshall, 2007;Chan, 2021). Dawson et al (2016) asserted that low levels of general inhibition, as a result of greater degrees of sensation-seeking and impulsivity, may lead to the development of atypical sexual interests.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…*The range of means in Chan 2021 appears based on the total number of items in the Paraphilia scale that load on to each paraphilic interest; thus, the range may exceed each individual item score (range of −3 to 3).…”
Section: Prevalencementioning
confidence: 99%
“…Other studies fail to assess whether the paraphilic interest and/or behavior caused distress, impairment, or entailed an actual risk of harm to others (e.g., Dawson et al, 2016; Seto et al, 2012), which is relevant to the paraphilic disorder diagnostic criteria. Last, measures have been limited in their assessment of only current or recent reports of paraphilic interests or acts, and do not assess across the lifespan (e.g., Chan, 2021; Dawson et al, 2016; Seto et al, 2012). The presence of paraphilias can aid in predicting the onset of sexual offending (Baur et al, 2016) and sexual reoffending (Mann et al, 2010), so it is necessary to have measurement tools that are psychometrically sound.…”
Section: Prevalencementioning
confidence: 99%